Multifunctional ecological anion environment-friendly wallpaper and preparation process thereof

By mixing zinc oxide and tourmaline and combining with polyurethane, combining graphene oxide with antibacterial substances to produce antibacterial wear-resistant components, forming a multi-layer structure of negative ion wallpaper, solving the problem of insufficient wear resistance and antibacterial properties of negative ion wallpapers. , achieving efficient air purification and long-term use effect.

CN119265998AInactive Publication Date: 2025-01-07HEBEI LUFA TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411473924.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing negative ion wallpaper has poor wear resistance and poor adhesion of negative ion powder, which leads to a short duration of release of negative ions, which cannot effectively purify the air, and is susceptible to moisture and mold and fall off, and cannot effectively kill bacteria.

Method used

A mixed ball mill of zinc oxide and tourmaline to produce negative ion powder, and a graft silane coupling agent is combined with polyurethane to form a polyurethane copolymer with high negative ion release properties, and a combination of graphene oxide and antibacterial substances are used to produce antibacterial and wear-resistant components. , curing through isothermal static pressure and ultraviolet light to form a multi-layered wallpaper.

Benefits of technology

It significantly improves the antibacterial properties, wear resistance and negative ion release properties of negative ion wallpaper, extends the service life, and enhances the purification effect of air, ensuring the green and environmentally friendly performance of the wallpaper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to multifunctional ecological negative ion environment-friendly wallpaper and a preparation process thereof, and belongs to the technical field of wallpaper, and the preparation process comprises the following steps: coating the surface of a base paper layer with a polyurethane copolymer with negative ion powder, and performing extrusion compounding in an isothermal static pressure manner to form a middle layer; an antibacterial wear-resistant component is sprayed on the surface of the middle layer, and is cured by ultraviolet irradiation to form an outer layer, so that the multifunctional ecological anion environment-friendly wallpaper consisting of the base paper layer, the middle layer and the outer layer is formed; zinc oxide and tourmaline are mixed and subjected to ball milling, and negative ion powder is obtained; grafting the negative ion powder with a silane coupling agent and then combining the negative ion powder with polyurethane to obtain a polyurethane copolymer with the negative ion powder; graphene oxide and an antibacterial substance are combined to prepare an antibacterial wear-resistant component; according to the technical scheme, the polyurethane copolymer with the negative ion powder improves the negative ion release performance of the wallpaper, the antibacterial and wear-resistant components enhance the antibacterial property and wear resistance of the wallpaper, and the overall comprehensive performance of the negative ion wallpaper is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wallpapers, and in particular, relates to a multifunctional ecological negative ion environmentally friendly wallpaper and a preparation process thereof. Background Art

[0002] Wallpaper has the main advantages of various colors, rich patterns, reasonable price, dirt resistance, and scrub resistance. It is a widely used indoor decoration material, which is widely used in indoor decoration of residences, offices, guesthouses, and hotels. Existing wallpapers are generally plastic wallpapers, metal wallpapers, non-woven wallpapers, fiberglass wallpapers, pulp wallpapers, wood fiber wallpapers, etc., which generally only have decorative effects and are relatively simple in function. Negative ion wallpaper is one of the functional wallpapers that has emerged in recent years. It can continuously release or generate negative ions, which can effectively eliminate the irritating gases such as benzene, formaldehyde, ketones, ammonia, etc. volatilized from the decorative materials used in the process of indoor decoration, as well as the odors caused by cigarettes in daily life, so that the air quality is improved. The released negative ions can not only sterilize and disinfect, but also have the ability to enhance the antioxidant and anti-aging properties of the human body and remove free radicals, protecting human health.

[0003] In the prior art, negative ion wallpaper is prepared by coating a coating containing negative ion powder on the wallpaper. Although the wallpaper has the function of releasing negative ions, the wallpaper has poor wear resistance, the interaction between the negative ion powder and the wallpaper is weak, and the adhesion is poor, resulting in a short duration of negative ion release and a limited number of negative ions generated, which cannot achieve the effect of effectively purifying the air. The existing negative ion wallpaper is easily affected by humid air, causing mold and even falling off, and cannot effectively kill microorganisms such as bacteria, which will cause damage to the wall surface in the long run. Therefore, the performance of negative ion wallpaper needs to be further improved. Summary of the invention

[0004] The purpose of the present invention is to provide a multifunctional ecological negative ion environmentally friendly wallpaper and a preparation process thereof, wherein zinc oxide and tourmaline are mixed and ball-milled to obtain negative ion powder; the mixing of zinc oxide and tourmaline can improve the negative ion release performance of tourmaline and increase the negative ion release amount of tourmaline, and after grinding, the particle size of the negative ion powder becomes smaller, which can further improve the negative ion release performance of the negative ion powder; after the negative ion powder is grafted with a silane coupling agent, it is combined with polyurethane through free radical polymerization to obtain a polyurethane copolymer with negative ion powder; the grafting of the negative ion powder with a silane coupling agent can improve the dispersibility of the negative ion powder, provide reaction sites for subsequent reactions, and further improve the negative ion release performance of the negative ion powder. The base polymer is combined with polyurethane to improve the binding force between the negative ion powder and the polyurethane; the antibacterial and wear-resistant components are prepared by combining graphene oxide with antibacterial substances; the antibacterial and wear-resistant properties of the negative ion wallpaper can be improved, and the negative ion release performance of the negative ion powder can also be improved; the surface of the base paper layer is coated with a polyurethane copolymer with negative ion powder, and is extruded and compounded by isothermal static pressing to form an intermediate layer; the antibacterial and wear-resistant components are sprayed on the surface of the intermediate layer, and ultraviolet light is used for curing to form an outer layer, thereby forming a multifunctional ecological negative ion environmentally friendly wallpaper consisting of a base paper layer, an intermediate layer and an outer layer; the prepared negative ion wallpaper has good negative ion release performance, antibacterial performance and wear resistance, and is green and environmentally friendly, with good comprehensive performance.

[0005] Technical problem to be solved by the present invention: In the prior art, negative ion wallpaper is prepared by coating a coating containing negative ion powder on the wallpaper. Although the wallpaper has the function of releasing negative ions, the wallpaper has poor wear resistance, the interaction between the negative ion powder and the wallpaper is weak, and the adhesion is poor, resulting in a short duration of negative ion release and a limited number of negative ions generated, which cannot achieve the effect of effectively purifying the air; the existing negative ion wallpaper is easily affected by humid air, causing mold and even falling off, and cannot effectively kill microorganisms such as bacteria, which will cause damage to the wall surface in the long run. Therefore, the performance of the negative ion wallpaper needs to be further improved.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A preparation process of a multifunctional ecological negative ion environmentally friendly wallpaper comprises the following steps: S1: coating a polyurethane copolymer containing negative ion powder on the surface of the base paper layer, and extruding and compounding the same by isothermal static pressing to form an intermediate layer; S2: spraying antibacterial and wear-resistant components on the surface of the middle layer, curing with ultraviolet light to form an outer layer, thereby forming a multifunctional ecological negative ion environmentally friendly wallpaper consisting of a base paper layer, a middle layer and an outer layer; The preparation method of the polyurethane copolymer with negative ion powder comprises the following steps: A1: Mix zinc oxide and tourmaline, and then ball-mill to obtain negative ion powder; A2: After grafting the anion powder with a silane coupling agent, it is combined with polyurethane through free radical polymerization to obtain a polyurethane copolymer with anion powder; The antibacterial and wear-resistant component is prepared by combining graphene oxide with antibacterial substances.

[0007] Furthermore, step A1 is specifically as follows: Zinc oxide, tourmaline and anhydrous ethanol are mixed and then placed in a stainless steel ball grinding jar. The ball mill speed is 300-500 rpm, the rotation direction is forward and reverse rotation for 5-10 minutes, and the grinding is 14-16 hours. After drying, negative ion powder is obtained.

[0008] Furthermore, the mass ratio of the zinc oxide, tourmaline and anhydrous ethanol is 0.5-1.5:2-3:10-20.

[0009] Furthermore, step A2 is specifically as follows: (1): Mix the negative ion powder and the silane coupling agent, adjust the pH value of the mixture to 8-9 with a sodium hydroxide solution, then add an ethanol / deionized water mixed solution, and react at 55-65°C for 1-2h, filter, wash with ethanol, and finally dry to obtain a silane-modified negative ion powder; (2): Mix the emulsified component and the silane-modified negative ion powder and stir for 1-2 hours to obtain system A. Mix the silane-modified negative ion powder and the vinyl-terminated polyurethane prepolymer and stir for 1-2 hours to obtain system B. Add the emulsified component and system B to system A, react at 55-65°C for 2-3 hours, then add system B and continue to react for 1-2 hours to obtain a polyurethane copolymer with negative ion powder.

[0010] In the above reaction process, the negative ion powder has hydroxyl groups, and the silane coupling agent has silanol groups after hydrolysis. The silanol groups on the silane coupling agent can be combined with the hydroxyl groups on the negative ion powder to obtain silane-modified negative ion powder; the silane coupling agent in the silane-modified negative ion powder has a carbon-carbon double bond, and the vinyl-terminated polyurethane prepolymer has a carbon-carbon double bond. The carbon-carbon double bond in the silane-modified negative ion powder can be combined with the carbon-carbon double bond on the vinyl-terminated polyurethane prepolymer through free radical copolymerization, and the silane-modified negative ion powder is grafted onto the vinyl-terminated polyurethane prepolymer to obtain a polyurethane copolymer with the negative ion powder.

[0011] Furthermore, in step (1), the silane coupling agent is composed of vinyl triethoxysilane and γ-glycidyloxypropyl trimethoxysilane mixed in a mass ratio of 1:1.

[0012] Furthermore, in step (1), the mass ratio of the negative ion powder to the silane coupling agent is 4-6:0.5-1.5.

[0013] Furthermore, in step (2), the emulsifying component is composed of sodium carboxymethyl cellulose, Tween 80, Span 60 and potassium persulfate mixed in a mass ratio of 3:7:3:0.2.

[0014] Furthermore, in step (2), the mass ratio of the emulsified component to the silane-modified anion powder is 13-14:17.5-18.5.

[0015] Further, the preparation method of the vinyl terminated polyurethane prepolymer comprises the following steps: Mix polyethylene glycol and hydroxyl-terminated polycaprolactone diol, stir for 25-35 minutes at 55-65°C in a nitrogen atmosphere, then add isophorone diisocyanate, heat to 75-85°C, stir and react for 2-4 hours, then cool to 55-65°C, add 2-hydroxyethyl acrylate and photoinitiator, and continue to react for 25-35 minutes to obtain a vinyl-terminated polyurethane prepolymer.

[0016] In the above reaction process, both ends of the polyethylene glycol and the hydroxyl-terminated polycaprolactone diol have hydroxyl groups, isophorone diisocyanate has an isocyanate group, and 2-hydroxyethyl acrylate has a hydroxyl group and a carbon-carbon double bond. The hydroxyl groups at both ends of the polyethylene glycol and the hydroxyl-terminated polycaprolactone diol can be combined with the isocyanate group at one end of isophorone diisocyanate, and the isocyanate group at the other end of isophorone diisocyanate can be combined with the hydroxyl group on 2-hydroxyethyl acrylate, and finally a vinyl-terminated polyurethane prepolymer is obtained.

[0017] Furthermore, the mass ratio of the hydroxyl-terminated polycaprolactone diol to isophorone diisocyanate is 1.5-2.5:0.5-1.5.

[0018] Furthermore, the photoinitiator is 1-hydroxycyclohexyl phenyl ketone.

[0019] Furthermore, the preparation method of the antibacterial and wear-resistant component comprises the following steps: The antibacterial substance is dissolved in an ethanol solution to obtain an antibacterial solution, graphene oxide is added to deionized water to obtain a suspension, the antibacterial solution and the suspension are mixed, stirred at room temperature for 22-24 hours, centrifuged, washed with deionized water, and finally vacuum dried at 75-85° C. to obtain an antibacterial and wear-resistant component.

[0020] Furthermore, the antibacterial substance is curcumin.

[0021] Furthermore, the mass ratio of the antibacterial substance to the ethanol solution is 0.02-0.06:30-50.

[0022] Furthermore, the mass ratio of the graphene oxide to deionized water is 0.05-0.15:80-120.

[0023] Furthermore, in step S1, the base paper layer is made of polyvinyl chloride fiber, bamboo fiber and polyester fiber in a mass ratio of 4:2:1, and then mixed and beaten, and the wallpaper is made according to the wallpaper making process, and the amount of the wallpaper is 70-80g / m 2 , and obtain the base paper layer.

[0024] Furthermore, in step S1, isothermal static pressing is used for extrusion compounding, with a temperature of 100-120° C. and a pressure of 4-6 MPa.

[0025] Furthermore, in step S1, the coating amount is 15-25 mL / cm 2 .

[0026] Furthermore, in step S2, ultraviolet light curing is used, the curing time is 1-2 hours, and the light intensity is 40-60W / cm 2 , temperature is 40-60℃, and ultraviolet light wavelength is 200-400nm.

[0027] Furthermore, in step S2, the spraying amount is 5-15 mL / cm 2 .

[0028] Beneficial effects of the present invention: (1) In the technical solution of the present invention, zinc oxide and tourmaline are mixed and ball-milled to obtain negative ion powder; tourmaline has the property of releasing negative ions. By mixing zinc oxide and tourmaline, zinc oxide can improve the negative ion release performance of tourmaline and increase the negative ion release amount of tourmaline. After grinding, the particle size of the negative ion powder becomes smaller, which can not only further improve the negative ion release performance of the negative ion powder, but also help to increase the specific surface area of ​​the negative ion powder, improve its surface activity and reactivity, and at the same time, its stability is good; after the negative ion powder is grafted with a silane coupling agent, it is then free radical polymerized with polyurethane to obtain a negative ion powder. Combined with the negative ion powder, a polyurethane copolymer with negative ion powder is obtained; the negative ion powder is grafted with silane coupling agent, which can not only improve the dispersibility and hydrophobicity of the negative ion powder and prevent it from agglomerating, but also the silane coupling agent has a carbon-carbon double bond, which can provide a reaction site for subsequent reactions. At the same time, the negative ion powder modified by the silane coupling agent can further improve the negative ion release performance of the negative ion powder. The silane-modified negative ion powder is combined with polyurethane through free radical polymerization, which improves the binding force between the negative ion powder and the polyurethane, further prolongs the time for the negative ion powder to release negative ions, and enhances the air purification effect of the negative ion wallpaper.

[0029] (2) In the technical scheme of the present invention, the antibacterial and wear-resistant component is prepared by combining graphene oxide with antibacterial substances; graphene oxide and antibacterial substances have a certain bactericidal effect on bacteria and other microorganisms. Combining graphene oxide with antibacterial substances can better improve the antibacterial properties of negative ion wallpapers. Graphene oxide has good mechanical properties, which can further improve the wear resistance of negative ion wallpapers and extend the service life of negative ion wallpapers. At the same time, graphene oxide has more hydroxyl and carboxyl groups, which can be better combined with the polyurethane copolymer with negative ion powder to enhance the adhesion between the two. Graphene oxide can also further improve the negative ion release performance of the negative ion powder and enhance the air purification effect of the negative ion wallpaper. The antibacterial and wear-resistant component effectively improves the antibacterial, mildew-proof and wear resistance of the negative ion wallpaper.

[0030] (3) In the technical scheme of the present invention, zinc oxide and tourmaline are mixed and ball-milled, and then a silane coupling agent is grafted, and then combined with polyurethane through free radical polymerization to obtain a polyurethane copolymer with negative ion powder; graphene oxide is combined with an antibacterial substance to obtain an antibacterial and wear-resistant component; the polyurethane copolymer with negative ion powder is coated on the surface of the base paper layer, and extruded and compounded by isothermal static pressing to form an intermediate layer; the antibacterial and wear-resistant component is sprayed on the surface of the intermediate layer, and cured by ultraviolet light to form an outer layer, thereby forming a multifunctional ecological negative ion environmentally friendly wallpaper consisting of a base paper layer, an intermediate layer and an outer layer; the obtained negative ion wallpaper has good negative ion release performance, antibacterial performance, wear resistance and mechanical properties, is green and environmentally friendly, and has good overall comprehensive performance. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The specific parameters of the raw materials used in the present invention are as follows: Zinc oxide, No.: Z820825, was provided by Shanghai McLean Biochemical Co., Ltd.; tourmaline, 4000 mesh, was purchased from Shanghai Huzheng Nanotechnology Co., Ltd.; graphene oxide, No.: S25040, was provided by Shanghai Yuanye Biotechnology Co., Ltd.; curcumin, No.: C805206, was provided by Shanghai McLean Biochemical Co., Ltd.

[0033] Example 1 The preparation of multifunctional ecological negative ion environmentally friendly wallpaper includes the following specific steps: S1: Coat the surface of the base paper layer with a polyurethane copolymer containing anion powder, and extrude and compound by isothermal static pressing at a temperature of 100°C and a pressure of 4MPa to form an intermediate layer, wherein the coating amount is 15mL / cm 2 The base paper layer is made of polyvinyl chloride fiber, bamboo fiber and polyester fiber in a mass ratio of 4:2:1. After being mixed and pulped, the wallpaper is made according to the wallpaper making process. The amount of wallpaper is 70g / m 2 , obtaining a base paper layer; S2: Spray antibacterial and wear-resistant components on the surface of the middle layer and cure them with ultraviolet light. The curing time is 1 hour and the light intensity is 40W / cm 2 , the temperature is 40℃, the wavelength of ultraviolet light is 200nm, and the outer layer is formed, thereby forming a multifunctional ecological negative ion environmentally friendly wallpaper consisting of a base paper layer, an intermediate layer and an outer layer. The spraying amount is 5mL / cm 2 ; The polyurethane copolymer with negative ion powder is prepared by the following specific steps: A1: According to the mass ratio of zinc oxide, tourmaline and anhydrous ethanol of 0.5:2:10, zinc oxide, tourmaline and anhydrous ethanol were mixed, and then placed in a stainless steel ball grinding tank (tank volume of 100mL), the ball-to-material ratio was set to 1:5, the ball mill speed was 300rpm, the rotation direction was forward and reverse rotation for 5min, grinding for 14h, and drying at 80℃ to obtain negative ion powder with a particle size of 470nm; A2: (1): According to the mass ratio of negative ion powder to silane coupling agent being 4:0.5, the negative ion powder and the silane coupling agent are mixed, the pH value of the mixture is adjusted to 8 with 0.1M sodium hydroxide solution, and then an ethanol / deionized water mixed solution is added (the volume ratio of ethanol to deionized water is 1:5, and the mass of the ethanol / deionized water mixed solution is 10 times the mass of the negative ion powder), and the mixture is reacted at 55°C for 1h, filtered, washed with ethanol for 3 times (the mass of ethanol each time is 4 times the mass of the negative ion powder), and finally dried to obtain a silane-modified negative ion powder, wherein the silane coupling agent is a mixture of vinyl triethoxysilane and γ-glycidyloxypropyl trimethoxysilane in a mass ratio of 1:1; (2): According to the mass ratio of the emulsifying component to the silane-modified anionic powder of 6.5:5.8, the emulsifying component and the silane-modified anionic powder were mixed and stirred for 1 hour to obtain system A. According to the mass ratio of the silane-modified anionic powder to the vinyl-terminated polyurethane prepolymer of 11.7:1.9, the silane-modified anionic powder and the vinyl-terminated polyurethane prepolymer were mixed and stirred for 1 hour to obtain system B. The emulsifying component, system B and system A were mixed in a mass ratio of 1:2:2, reacted at 55°C for 2 hours, and then an equal mass of system B was added and the reaction was continued for 1 hour to obtain a polyurethane copolymer with anionic powder, wherein the emulsifying component is composed of sodium carboxymethyl cellulose, Tween 80, Span 60 and potassium persulfate mixed in a mass ratio of 3:7:3:0.2; Wherein, the preparation method of vinyl terminated polyurethane prepolymer comprises the following steps: According to the mass ratio of polyethylene glycol, hydroxyl-terminated polycaprolactone diol and isophorone diisocyanate being 0.5:1:0.5, polyethylene glycol and hydroxyl-terminated polycaprolactone diol were mixed, stirred for 25 minutes at 55° C. in a nitrogen atmosphere, then isophorone diisocyanate was added, the temperature was raised to 75° C., and stirred for reaction for 2 hours, then the temperature was lowered to 55° C., 2-hydroxyethyl acrylate (the mass of 2-hydroxyethyl acrylate was 45wt% of the mass of isophorone diisocyanate) and 1-hydroxycyclohexyl phenyl ketone (the mass of 1-hydroxycyclohexyl phenyl ketone was 1wt% of the mass of isophorone diisocyanate) were added, and the reaction was continued for 25 minutes to obtain a vinyl-terminated polyurethane prepolymer; The preparation of the antibacterial and wear-resistant component comprises the following specific steps: Curcumin was dissolved in 50% ethanol solution at a mass ratio of curcumin to ethanol solution of 0.02:30 to obtain an antibacterial solution, graphene oxide was added to deionized water at a mass ratio of graphene oxide to deionized water of 0.05:80 to obtain a suspension, the antibacterial solution was mixed with the suspension, stirred at room temperature for 22 hours, centrifuged at 4000 rpm for 5 minutes, washed with deionized water, and finally vacuum dried at 75°C for 24 hours to obtain an antibacterial and wear-resistant component.

[0034] Example 2 The preparation of multifunctional ecological negative ion environmentally friendly wallpaper includes the following specific steps: S1: Coat the surface of the base paper layer with a polyurethane copolymer containing anion powder, and extrude and compound by isothermal static pressing at a temperature of 110°C and a pressure of 5MPa to form an intermediate layer, wherein the coating amount is 20mL / cm 2 The base paper layer is made of polyvinyl chloride fiber, bamboo fiber and polyester fiber in a mass ratio of 4:2:1. After being mixed and pulped, the wallpaper is made according to the wallpaper making process. The amount of wallpaper is 75g / m 2 , obtaining a base paper layer; S2: Spray antibacterial and wear-resistant components on the surface of the middle layer and cure with ultraviolet light. The curing time is 1.5 hours and the light intensity is 50W / cm 2 , the temperature is 50℃, the wavelength of ultraviolet light is 300nm, and the outer layer is formed, thereby forming a multifunctional ecological negative ion environmentally friendly wallpaper consisting of a base paper layer, an intermediate layer and an outer layer, wherein the spraying amount is 10mL / cm 2 ; The polyurethane copolymer with negative ion powder is prepared by the following specific steps: A1: According to the mass ratio of zinc oxide, tourmaline and anhydrous ethanol of 1:2.5:15, zinc oxide, tourmaline and anhydrous ethanol were mixed, and then placed in a stainless steel ball grinding tank (tank volume of 100mL), the ball-to-material ratio was set to 1:5, the ball mill speed was 400rpm, the rotation direction was forward and reverse rotation for 8min, grinding for 15h, and dried at 80℃ to obtain negative ion powder with a particle size of 460nm; A2: (1): Mix the negative ion powder and the silane coupling agent in a mass ratio of 5:1, adjust the pH value of the mixture to 8.5 with 0.1M sodium hydroxide solution, then add an ethanol / deionized water mixed solution (the volume ratio of ethanol to deionized water is 1:5, and the mass of the ethanol / deionized water mixed solution is 10 times the mass of the negative ion powder), and react at 60°C for 1.5h, filter, wash with ethanol three times (the mass of ethanol each time is 4 times the mass of the negative ion powder), and finally dry to obtain a silane-modified negative ion powder, wherein the silane coupling agent is a mixture of vinyl triethoxysilane and γ-glycidyloxypropyl trimethoxysilane in a mass ratio of 1:1; (2): According to the mass ratio of the emulsifying component to the silane-modified anionic powder of 6.7:6, the emulsifying component and the silane-modified anionic powder were mixed and stirred for 1.5 hours to obtain system A; according to the mass ratio of the silane-modified anionic powder to the vinyl-terminated polyurethane prepolymer of 12:2, the silane-modified anionic powder and the vinyl-terminated polyurethane prepolymer were mixed and stirred for 1.5 hours to obtain system B; the emulsifying component, system B and system A were mixed in a mass ratio of 1:2:2, reacted at 60°C for 2.5 hours, and then an equal mass of system B was added and the reaction was continued for 1.5 hours to obtain a polyurethane copolymer with anionic powder, wherein the emulsifying component is composed of sodium carboxymethyl cellulose, Tween 80, Span 60 and potassium persulfate mixed in a mass ratio of 3:7:3:0.2; Wherein, the preparation method of vinyl terminated polyurethane prepolymer comprises the following steps: According to the mass ratio of polyethylene glycol, hydroxyl-terminated polycaprolactone diol and isophorone diisocyanate being 1:1.5:1, polyethylene glycol and hydroxyl-terminated polycaprolactone diol are mixed, stirred for 30 minutes at 60°C in a nitrogen atmosphere, and then isophorone diisocyanate is added, the temperature is raised to 80°C, and stirred for reaction for 3 hours, and then the temperature is lowered to 60°C, and 2-hydroxyethyl acrylate (the mass of 2-hydroxyethyl acrylate is 45wt% of the mass of isophorone diisocyanate) and 1-hydroxycyclohexyl phenyl ketone (the mass of 1-hydroxycyclohexyl phenyl ketone is 1wt% of the mass of isophorone diisocyanate) are added, and the reaction is continued for 30 minutes to obtain a vinyl-terminated polyurethane prepolymer; The preparation of the antibacterial and wear-resistant component comprises the following specific steps: According to the mass ratio of curcumin to ethanol solution of 0.04:40, curcumin was dissolved in 50% ethanol solution to obtain an antibacterial solution, and according to the mass ratio of graphene oxide to deionized water of 0.1:100, graphene oxide was added to deionized water to obtain a suspension, the antibacterial solution and the suspension were mixed, stirred at room temperature for 23 hours, centrifuged at 3000 rpm for 8 minutes, washed with deionized water, and finally vacuum dried at 80°C for 24 hours to obtain an antibacterial and wear-resistant component.

[0035] Example 3 The preparation of multifunctional ecological negative ion environmentally friendly wallpaper includes the following specific steps: S1: The surface of the base paper layer is coated with a polyurethane copolymer containing anion powder, and extruded by isothermal static pressing at a temperature of 120°C and a pressure of 6MPa to form an intermediate layer, wherein the coating amount is 25mL / cm 2 The base paper layer is made of polyvinyl chloride fiber, bamboo fiber and polyester fiber in a mass ratio of 4:2:1. After being mixed and pulped, the wallpaper is made according to the wallpaper making process. The amount of wallpaper is 80g / m 2 , obtaining a base paper layer; S2: Spray antibacterial and wear-resistant components on the surface of the middle layer and cure with ultraviolet light for 2 hours at a light intensity of 60W / cm 2 , the temperature is 60℃, the wavelength of ultraviolet light is 400nm, and the outer layer is formed, thereby forming a multifunctional ecological negative ion environmentally friendly wallpaper consisting of a base paper layer, an intermediate layer and an outer layer. The spraying amount is 15mL / cm 2 ; The polyurethane copolymer with negative ion powder is prepared by the following specific steps: A1: According to the mass ratio of zinc oxide, tourmaline and anhydrous ethanol of 1.5:3:20, zinc oxide, tourmaline and anhydrous ethanol were mixed, and then placed in a stainless steel ball grinding tank (tank volume of 100mL), the ball-to-material ratio was set to 1:5, the ball mill speed was 500rpm, the rotation direction was forward and reverse rotation for 10min, grinding for 16h, and dried at 80℃ to obtain negative ion powder with a particle size of 450nm; A2: (1): Mix the negative ion powder and the silane coupling agent in a mass ratio of 6:1.5, adjust the pH value of the mixture to 9 with a 0.1M sodium hydroxide solution, then add an ethanol / deionized water mixed solution (the volume ratio of ethanol to deionized water is 1:5, and the mass of the ethanol / deionized water mixed solution is 10 times the mass of the negative ion powder), and react at 65°C for 2h, filter, wash with ethanol three times (the mass of ethanol each time is 4 times the mass of the negative ion powder), and finally dry to obtain a silane-modified negative ion powder, wherein the silane coupling agent is a mixture of vinyl triethoxysilane and γ-glycidyloxypropyl trimethoxysilane in a mass ratio of 1:1; (2): According to the mass ratio of the emulsifying component to the silane-modified anionic powder of 7:6.2, the emulsifying component and the silane-modified anionic powder were mixed and stirred for 2 hours to obtain system A; according to the mass ratio of the silane-modified anionic powder to the vinyl-terminated polyurethane prepolymer of 12.3:2.1, the silane-modified anionic powder and the vinyl-terminated polyurethane prepolymer were mixed and stirred for 2 hours to obtain system B; the emulsifying component, system B and system A were mixed in a mass ratio of 1:2:2, reacted at 65°C for 3 hours, and then an equal mass of system B was added and the reaction was continued for 2 hours to obtain a polyurethane copolymer with anionic powder, wherein the emulsifying component is composed of sodium carboxymethyl cellulose, Tween 80, Span 60 and potassium persulfate mixed in a mass ratio of 3:7:3:0.2; Wherein, the preparation method of vinyl terminated polyurethane prepolymer comprises the following steps: According to the mass ratio of polyethylene glycol, hydroxyl-terminated polycaprolactone diol and isophorone diisocyanate being 1.5:2:1.5, polyethylene glycol and hydroxyl-terminated polycaprolactone diol were mixed, stirred for 35 minutes at 65°C in a nitrogen atmosphere, and then isophorone diisocyanate was added, the temperature was raised to 85°C, and the mixture was stirred for reaction for 4 hours, and then the temperature was lowered to 65°C, and 2-hydroxyethyl acrylate (the mass of 2-hydroxyethyl acrylate was 45wt% of the mass of isophorone diisocyanate) and 1-hydroxycyclohexyl phenyl ketone (the mass of 1-hydroxycyclohexyl phenyl ketone was 1wt% of the mass of isophorone diisocyanate) were added, and the reaction was continued for 35 minutes to obtain a vinyl-terminated polyurethane prepolymer; The preparation of the antibacterial and wear-resistant component comprises the following specific steps: Curcumin was dissolved in 50% ethanol solution at a mass ratio of curcumin to ethanol solution of 0.06:50 to obtain an antibacterial solution, graphene oxide was added to deionized water at a mass ratio of graphene oxide to deionized water of 0.15:120 to obtain a suspension, the antibacterial solution was mixed with the suspension, stirred at room temperature for 24 hours, centrifuged at 2000 rpm for 10 minutes, washed with deionized water, and finally vacuum dried at 85°C for 24 hours to obtain an antibacterial and wear-resistant component.

[0036] Comparative Example 1 The difference between this comparative example and Example 3 is that when preparing the polyurethane copolymer with negative ion powder, the mass of zinc oxide in step A1 is replaced by aluminum oxide, and the remaining steps and raw materials are the same as those in Example 3; A1: Alumina, tourmaline and anhydrous ethanol were mixed in a mass ratio of 1.5:3:20, and then placed in a stainless steel ball grinding jar (tank volume of 100 mL), the ball-to-material ratio was set to 1:5, the ball mill speed was 500 rpm, the rotation direction was forward and reverse rotation for 10 min, grinding for 16 h, and dried at 80 ° C to obtain negative ion powder with a particle size of 450 nm.

[0037] Comparative Example 2 The difference between this comparative example and Example 3 is that when preparing the polyurethane copolymer with negative ion powder, the mass of the silane coupling agent in step (1) of A2 is replaced by vinyl triethoxysilane, and the remaining steps and raw materials are the same as those in Example 3; A2: (1): Mix the negative ion powder and vinyl triethoxysilane in a mass ratio of 6:1.5, adjust the pH value of the mixture to 9 with 0.1 M sodium hydroxide solution, then add ethanol / deionized water mixed solution (the volume ratio of ethanol to deionized water is 1:5, and the mass of the ethanol / deionized water mixed solution is 10 times the mass of the negative ion powder), and react at 65°C for 2h. After filtering, wash with ethanol three times (the mass of ethanol each time is 4 times the mass of the negative ion powder), and finally dry to obtain silane-modified negative ion powder.

[0038] Comparative Example 3 The difference between this comparative example and Example 3 is that when preparing the polyurethane copolymer with anion powder, the emulsified component, silane-modified anion powder and vinyl-terminated polyurethane prepolymer in step (2) of A2 are directly mixed and reacted, and the remaining steps and raw materials are synchronized with Example 3; A2: (2): According to the mass ratio of emulsifying component, silane modified anion powder and vinyl terminated polyurethane prepolymer being 14:18.5:2.1, the emulsifying component, silane modified anion powder and vinyl terminated polyurethane prepolymer are mixed, stirred for 2 hours, and reacted at 65°C for 5 hours to obtain a polyurethane copolymer with anion powder, wherein the emulsifying component is composed of sodium carboxymethyl cellulose, Tween 80, Span 60 and potassium persulfate mixed in the mass ratio of 3:7:3:0.2.

[0039] Comparative Example 4 The difference between this comparative example and Example 3 is that when preparing the vinyl-terminated polyurethane prepolymer, the mass of isophorone diisocyanate is replaced by toluene-2,4-diisocyanate, and the remaining steps and raw materials are the same as those of Example 3; The preparation method of the vinyl terminated polyurethane prepolymer comprises the following steps: Polyethylene glycol and hydroxyl-terminated polycaprolactone diol were mixed according to a mass ratio of polyethylene glycol, hydroxyl-terminated polycaprolactone diol and toluene-2,4-diisocyanate of 1.5:2:1.5, stirred for 35 minutes at 65°C in a nitrogen atmosphere, then toluene-2,4-diisocyanate was added, the temperature was raised to 85°C, and the reaction was stirred for 4 hours, then the temperature was lowered to 65°C, 2-hydroxyethyl acrylate (the mass of 2-hydroxyethyl acrylate was 45wt% of the mass of toluene-2,4-diisocyanate) and 1-hydroxycyclohexyl phenyl ketone (the mass of 1-hydroxycyclohexyl phenyl ketone was 1wt% of the mass of toluene-2,4-diisocyanate) were added, and the reaction was continued for 35 minutes to obtain a vinyl-terminated polyurethane prepolymer.

[0040] Comparative Example 5 The difference between this comparative example and Example 3 is that when preparing the vinyl-terminated polyurethane prepolymer, polyethylene glycol is combined with isophorone diisocyanate, and the remaining steps and raw materials are the same as those in Example 3; The preparation method of the vinyl terminated polyurethane prepolymer comprises the following steps: According to the mass ratio of polyethylene glycol to isophorone diisocyanate being 2.5:1.5, polyethylene glycol was stirred at 65°C in a nitrogen atmosphere for 35 minutes, and then isophorone diisocyanate was added, the temperature was raised to 85°C, and the reaction was stirred for 4 hours, and then the temperature was lowered to 65°C, and 2-hydroxyethyl acrylate (the mass of 2-hydroxyethyl acrylate is 45wt% of the mass of isophorone diisocyanate) and 1-hydroxycyclohexyl phenyl ketone (the mass of 1-hydroxycyclohexyl phenyl ketone is 1wt% of the mass of isophorone diisocyanate) were added, and the reaction was continued for 35 minutes to obtain a vinyl-terminated polyurethane prepolymer.

[0041] Comparative Example 6 The difference between this comparative example and Example 3 is that when preparing the antibacterial and wear-resistant component, the mass of graphene oxide is replaced by graphene, and the remaining steps and raw materials are synchronized with Example 3; The preparation of the antibacterial and wear-resistant component comprises the following specific steps: According to the mass ratio of curcumin to ethanol solution of 0.06:50, curcumin was dissolved in 50% ethanol solution to obtain an antibacterial solution, and according to the mass ratio of graphene to deionized water of 0.15:120, graphene was added to deionized water to obtain a suspension, the antibacterial solution and the suspension were mixed, stirred at room temperature for 24 hours, centrifuged at 2000 rpm for 10 minutes, washed with deionized water, and finally vacuum dried at 85°C for 24 hours to obtain an antibacterial and wear-resistant component.

[0042] The multifunctional ecological negative ion environmentally friendly wallpapers prepared in Examples 1-3 and Comparative Examples 1-6 are now tested for antibacterial performance, antibacterial persistence, tensile strength, wear resistance and negative ion release performance; the antibacterial performance test is carried out according to GB / T 21866-2008, and the bacterial species are Staphylococcus aureus and Escherichia coli; the antibacterial persistence test is as follows: the multifunctional ecological negative ion environmentally friendly wallpapers prepared in Examples 1-3 and Comparative Examples 1-6 are irradiated with an ultraviolet lamp with a wavelength of 253.7nm for 100 hours and then the antibacterial rate is tested; the tensile strength test is carried out according to GB / T 12914-2018; the wear resistance test is carried out according to GB / T 23988-2009; the negative ion release performance test is carried out according to GB / T 34844-2017, and the negative ion release amount is measured by an air negative ion measuring instrument. The test results are shown in Tables 1 and 2 below: Table 1 Antibacterial properties of the multifunctional ecological negative ion environmentally friendly wallpapers prepared in Examples 1-3 and Comparative Examples 1-6

[0043] Table 2 Tensile strength, wear resistance and negative ion release performance of the multifunctional ecological negative ion environmentally friendly wallpapers prepared in Examples 1-3 and Comparative Examples 1-6

[0044] It can be seen from the data in Table 1 and Table 2 above, and from the comparison between Comparative Examples 1-2 and Example 3, it can be seen that the test results of preparing multifunctional ecological negative ion environmentally friendly wallpaper by replacing the mass of zinc oxide in step A1 with aluminum oxide or replacing the mass of the silane coupling agent in step (1) in A2 with vinyl triethoxysilane are worse than those of Example 3, indicating that combining zinc oxide with tourmaline to prepare negative ion powder can effectively improve the negative ion release performance of tourmaline, and combining the silane coupling agent composed of a mixture of vinyl triethoxysilane and γ-glycidyloxypropyl trimethoxysilane with the negative ion powder can not only improve the dispersibility of the negative ion powder and enhance the adhesion between the negative ion powder and the wallpaper, but also can better improve the negative ion release performance of the wallpaper, and further improve the tensile strength and antibacterial performance of the wallpaper; From the comparison between Comparative Example 3 and Example 3, it can be seen that the test result of preparing the multifunctional ecological negative ion environmentally friendly wallpaper by directly mixing the emulsified components of step (2) in A2, the silane-modified negative ion powder and the vinyl-terminated polyurethane prepolymer is worse than that of Example 3, indicating that the emulsified components are added step by step to the silane-modified negative ion powder and the vinyl-terminated polyurethane prepolymer, which can better control the reaction rate and maintain the stability of the emulsion system, thereby forming a polyurethane copolymer with better performance, thereby further improving the mechanical properties, negative ion release performance and wear resistance of the negative ion wallpaper; From the comparison of Comparative Examples 4-5 and Example 3, it can be seen that the test results of the multifunctional ecological negative ion environmentally friendly wallpaper prepared by replacing the mass of isophorone diisocyanate with toluene-2,4-diisocyanate or combining polyethylene glycol with isophorone diisocyanate are poorer than those of Example 3, indicating that the combination of isophorone diisocyanate, hydroxyl-terminated polycaprolactone diol and polyethylene glycol, and then combining with 2-hydroxyethyl acrylate to obtain a vinyl-terminated polyurethane prepolymer can better improve the interfacial bonding force between the vinyl-terminated polyurethane prepolymer and the silane-modified negative ion powder, increase the adhesion between the polyurethane copolymer with the negative ion powder and the base paper layer, and further improve the mechanical properties, wear resistance and negative ion release performance of the negative ion wallpaper; From the comparison between Comparative Example 6 and Example 3, it can be seen that the test result of preparing multifunctional ecological negative ion environmentally friendly wallpaper by replacing the mass of graphene oxide with graphene is worse than that of Example 3, indicating that by combining graphene oxide with curcumin, graphene oxide can better load curcumin, effectively improve the antibacterial performance and antibacterial durability of the negative ion wallpaper, and further improve the wear resistance, mechanical properties and negative ion release performance of the wallpaper, increase its negative ion release amount, and extend the service life of the wallpaper.

[0045] It can be seen from Table 1 and Table 2 above that the multifunctional ecological negative ion environmentally friendly wallpaper prepared in Examples 1-3 is compared with the multifunctional ecological negative ion environmentally friendly wallpaper prepared in Comparative Examples 1-6. The polyurethane copolymer with negative ion powder is obtained by mixing zinc oxide and tourmaline for ball milling, then grafting silane coupling agent, and then combining with polyurethane; graphene oxide is combined with antibacterial substance to obtain antibacterial and wear-resistant components; the polyurethane copolymer with negative ion powder is coated on the surface of the base paper layer to form an intermediate layer; the antibacterial and wear-resistant components are sprayed on the surface of the intermediate layer to form an outer layer, thereby forming a multifunctional ecological negative ion environmentally friendly wallpaper consisting of a base paper layer, an intermediate layer and an outer layer, which meets the test performance requirements, while the multifunctional ecological negative ion environmentally friendly wallpaper prepared in Comparative Examples 1-6 does not meet the performance requirements. This shows that the multifunctional ecological negative ion environmentally friendly wallpaper prepared by the present invention not only has good mechanical properties, negative ion release performance, wear resistance, antibacterial performance and antibacterial durability, but is also green and environmentally friendly, and has good comprehensive performance.

[0046] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0047] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A preparation process of a multifunctional ecological negative ion environmentally friendly wallpaper, characterized in that: The following steps are involved: S1: coating a polyurethane copolymer containing negative ion powder on the surface of the base paper layer, and extruding and compounding the same by isothermal static pressing to form an intermediate layer; S2: spraying antibacterial and wear-resistant components on the surface of the middle layer, curing with ultraviolet light to form an outer layer, thereby forming a multifunctional ecological negative ion environmentally friendly wallpaper consisting of a base paper layer, a middle layer and an outer layer; The preparation method of the polyurethane copolymer with negative ion powder comprises the following steps: A1: Mix zinc oxide and tourmaline, and then ball-mill to obtain negative ion powder; A2: After grafting the anion powder with a silane coupling agent, it is combined with polyurethane through free radical polymerization to obtain a polyurethane copolymer with anion powder; The antibacterial and wear-resistant component is prepared by combining graphene oxide with antibacterial substances.

2. The preparation process of a multifunctional ecological negative ion environmentally friendly wallpaper according to claim 1, characterized in that: Step A1 is specifically as follows: Zinc oxide, tourmaline and anhydrous ethanol are mixed and then placed in a stainless steel ball grinding jar. The ball mill speed is 300-500 rpm, the rotation direction is forward and reverse rotation for 5-10 minutes, and the grinding is 14-16 hours. After drying, negative ion powder is obtained.

3. The preparation process of a multifunctional ecological negative ion environmentally friendly wallpaper according to claim 2, characterized in that: The mass ratio of the zinc oxide, tourmaline and anhydrous ethanol is 0.5-1.5:2-3:10-20.

4. The preparation process of a multifunctional ecological negative ion environmentally friendly wallpaper according to claim 1, characterized in that: Step A2 is specifically as follows: (1): Mix the negative ion powder and the silane coupling agent, adjust the pH value of the mixture to 8-9 with a sodium hydroxide solution, then add an ethanol / deionized water mixed solution, and react at 55-65°C for 1-2h, filter, wash with ethanol, and finally dry to obtain a silane-modified negative ion powder; (2): Mix the emulsified component and the silane-modified negative ion powder and stir for 1-2 hours to obtain system A. Mix the silane-modified negative ion powder and the vinyl-terminated polyurethane prepolymer and stir for 1-2 hours to obtain system B. Add the emulsified component and system B to system A, react at 55-65°C for 2-3 hours, then add system B and continue to react for 1-2 hours to obtain a polyurethane copolymer with negative ion powder.

5. The preparation process of a multifunctional ecological negative ion environmentally friendly wallpaper according to claim 4, characterized in that: In step (1), the silane coupling agent is composed of vinyl triethoxysilane and γ-glycidyloxypropyl trimethoxysilane mixed in a mass ratio of 1:

1.

6. The preparation process of a multifunctional ecological negative ion environmentally friendly wallpaper according to claim 4, characterized in that: In step (2), the method for preparing the vinyl terminated polyurethane prepolymer comprises the following steps: Mix polyethylene glycol and hydroxyl-terminated polycaprolactone diol, stir for 25-35 minutes at 55-65°C in a nitrogen atmosphere, then add isophorone diisocyanate, heat to 75-85°C, stir and react for 2-4 hours, then cool to 55-65°C, add 2-hydroxyethyl acrylate and photoinitiator, and continue to react for 25-35 minutes to obtain a vinyl-terminated polyurethane prepolymer.

7. The preparation process of a multifunctional ecological negative ion environmentally friendly wallpaper according to claim 6, characterized in that: The photoinitiator is 1-hydroxycyclohexyl phenyl ketone.

8. The preparation process of a multifunctional ecological negative ion environmentally friendly wallpaper according to claim 1, characterized in that: The preparation method of the antibacterial and wear-resistant component comprises the following steps: The antibacterial substance is dissolved in an ethanol solution to obtain an antibacterial solution, graphene oxide is added to deionized water to obtain a suspension, the antibacterial solution and the suspension are mixed, stirred at room temperature for 22-24 hours, centrifuged, washed with deionized water, and finally vacuum dried at 75-85° C. to obtain an antibacterial and wear-resistant component.

9. The preparation process of a multifunctional ecological negative ion environmentally friendly wallpaper according to claim 8, characterized in that: The antibacterial substance is curcumin.

10. A multifunctional ecological negative ion environmentally friendly wallpaper made by the preparation process as described in any one of claims 1 to 9.

Citation Information

Cited By

  • High-pressure plastic-wood plate capable of releasing negative ions as well as preparation process and application of high-pressure plastic-wood plate

    CN120365759A

  • High-pressure plastic-wood board capable of releasing negative ions and preparation process and application thereof

    CN120365759B